The Analytical Study of the Role of the Holy Prophet Muhammad (صلی اللہ علیہ وسلم) in the Development of Islamic Culture and Civilization - Tahira Basharat; Imran Hayat (Pakistan Journal of Islamic Research)
The article attempts to analyse the role of the Holy Prophet Muhammad (peace be upon him) in the development of Islamic culture and civilization. It aims to highlight the teachings of the Holy Prophet Muhammad (peace be upon him) that shifted the social, political, intellectual, and religious paradigms. These seerat-based doctrines promulgated the core socio-cultural values of justice, mercy, equality, and ethical behaviour and reformed society. The moral and ethical values stimulated sincerity, selflessness, and kindness and replaced the old tribal and savage system of the Arabian society. The holy Prophet Muhammad (peace be upon him) mediated among the hostile Arab tribes and created a peaceful and plural state that reveal his diplomatic excellence. He prioritized the acquisition of knowledge by declaring it compulsory for all Muslim men and women and introduced Islamic ethics related to family, marriage, and interpersonal relationships. Subsequently, Islamic scholars and researchers made advances in the fields of religion, philosophy, medicine, mathematics, and the translation and preservation of antiquity on the foundations laid by the Holy Prophet (peace be upon him) that still have relevance in the modern world. The study finds that the Holy Prophet’s contribution to cultural and civilizational development bears historical importance and transcends the barriers of time and space.